2008
DOI: 10.1007/s00267-008-9145-z
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Impact Due to the Use of Combustible Fuels: Life Cycle Viewpoint and Relative Radiative Forcing Commitment

Abstract: Extensive information on the greenhouse impacts of various human actions is important in developing effective climate change mitigation strategies. The greenhouse impacts of combustible fuels consist not only of combustion emissions but also of emissions from the fuel production chain and possible effects on the ecosystem carbon storages. It is important to be able to assess the combined, total effect of these different emissions and to express the results in a comprehensive way. In this study, a new concept c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 12 publications
0
55
0
1
Order By: Relevance
“…Using forest residues gave consistently lower radiative forcing than using coal, although using fossil gas gave lower radiative forcing for the first 15-20 years, after which forest residues gave lower radiative forcing. Kirkinen et al [12] introduced the concept of relative radiative forcing commitment (RRFC), which they defined as the ratio of energy absorbed in the Earth system due to radiative forcing caused by GHGs from production and combustion of a fuel, compared to the energy released by the combustion of fuel. They found that the RRFC of fossil fuels continue to rise over a 300-year time horizon, while the RRFC of slash stabilizes after about 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Using forest residues gave consistently lower radiative forcing than using coal, although using fossil gas gave lower radiative forcing for the first 15-20 years, after which forest residues gave lower radiative forcing. Kirkinen et al [12] introduced the concept of relative radiative forcing commitment (RRFC), which they defined as the ratio of energy absorbed in the Earth system due to radiative forcing caused by GHGs from production and combustion of a fuel, compared to the energy released by the combustion of fuel. They found that the RRFC of fossil fuels continue to rise over a 300-year time horizon, while the RRFC of slash stabilizes after about 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Holmgren et al (2007) compared the radiative forcing effects of using fossil fuels or forest residues for energy, considering the time dynamics of biomass decay if residues are left in the forest. Kirkinen et al (2008Kirkinen et al ( , 2009) introduced a ''relative radiative forcing commitment'' which is the cumulative radiative forcing caused by using a fuel relative to the combustion energy of the fuel, and used the measure to compare several fossil fuels and biofuels. Bird (2009) discussed the issues of timing of CO 2 emissions of biomass systems, and suggested that cumulative radiative forcing is an appropriate measure of climate impacts in life cycle assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, carbon balance calculations that assume that the growing forest offsets the ‘upfront’ bioenergy emissions result in an overestimation of the true climate change mitigation potential of forest bioenergy (Kendall et al ., ; Cherubini et al ., ; Pingoud et al ., ). In order to take account of both the time‐dependence of the GHG fluxes and the atmospheric residence times of GHGs, the potential climate impact impacts must be assessed with a more comprehensive metric than the carbon balance calculations alone, such as radiative forcing (RF) (Zetterberg et al ., ; Holmgren et al ., ; Kirkinen et al ., ; Sathre & Gustavsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Forest residue bioenergy has a warming impact on the climate because of the timing of the emissions and the slow removal of CO 2 from the atmosphere (Zetterberg et al ., ; Holmgren et al ., ; Kirkinen et al ., ; Sathre & Gustavsson, ; Repo et al ., ). Therefore, carbon balance calculations that assume that the growing forest offsets the ‘upfront’ bioenergy emissions result in an overestimation of the true climate change mitigation potential of forest bioenergy (Kendall et al ., ; Cherubini et al ., ; Pingoud et al ., ).…”
Section: Introductionmentioning
confidence: 99%